Liquid sample introduction in ICP spectrometry : a practical guide - Todoli, Jose-Luis (Elsevier, 2008)
Inductively coupled plasma atomic or mass spectrometry is one of the most common technique for elemental analysis. Samples to be analyzed are usually in the form of solutions and need to be introduced into the plasma by means of a sample introduction system, so as to obtain a mist of very fine droplets. Because the sample introduction system can be a limiting factor in the analytical performance, it is crucial to optimize its design and its use. It is the purpose of this book to provide fundamental knowledge along with practical use to obtain the best of the technique. - Fundamental as well as practical character -Troubleshooting section - Flow charts with optimum systems to be used for a given application.